A Discussion With Sandy O’Sullivan About Key Issues for the Australian Indigenous Studies Learning and Teaching Network - Barney, Katelyn (The Australian Journal of Indigenous Education, 2014)
This article takes the form of an interview with Sandy O’Sullivan, who is a partner on the Australian Indigenous Studies Learning and Teaching Network, about key issues that have arisen through Network discussions. She is a Wiradjuri woman and a Senior Aboriginal researcher at the Batchelor Institute of Indigenous Tertiary Education. O’Sullivan emphasises the strengths of the Network and difficulties the Network participants have had in defining ‘Indigenous Studies’. She also discusses the important work for the Network to do into the future, to continue to strengthen relationships between educators and improve teaching and learning of Indigenous Studies at tertiary level.